From Preschool to Prosperity : The Economic Payoff to Early Childhood Education - Bartik, Timothy J.; Project Muse. (Kalamazoo, Michigan : W.E. Upjohn Institute for Employment Research, 2014)
This Bbook explores the economic payoffs to investment in early childhood education.
Introduction : What are early childhood education programs? ; What are the benefits from early childhood education? ; How can early childhood education affect the child's future life course? ; A proposal for early childhood education ; The plan of the book -- 2. What is the evidence on the earnings effects of high-quality early childhood education, and why should we believe it? : Why the research evidence for early childhood education is credible ; Random assignment studies ; Other long-term studies with good comparison groups: Head Start ; The Chicago Child-Parent Center Program ; Predicting long-term earnings effects from short-term test score effects ; Infant health and development program ; North Carolina's Smart Start Program, and more at four ; State and local pre-K programs: the regression discontinuity evidence ; Summary of the evidence -- 3. How do the adult earnings benefits of high-quality early childhood education compare to costs? : Future earnings versus present costs ; Parental earnings ; Are these effects large? ; Closing comments -- 4. Criticisms of the research evidence : Criticism 1: The evidence for early childhood education's benefits only comes from small and expensive experiments run a long time ago ; Criticism 2: Early childhood education is argued to be ineffective because the recent Head Start experiment has test score effects that quickly faded to statistical insignificance ; Criticism 3: Why haven't Oklahoma and Georgia, two states that have prominently adopted universal pre-K, been more obviously successful in improving test scores and other social indicators? ; Criticism 4: The recent Tennessee pre-K experiment shows that test score effects quickly fade, which raises questions about whether state pre-K programs are effective ; Concluding comments -- 5. How can early childhood education programs best be designed? : Quality of teacher-child interactions ; Class size and teacher credentials ; Middle-class children ; Program duration ; Earlier versus later interventions -- 6. Spillover benefits: how does early childhood education affect other groups than those families directly served by these programs? : Skill spillovers ; Peer effects in education ; Spillovers from reducing crime ; Government/taxpayer benefits ; Pre-K: the next generation ; Concluding comments -- 7. A proposed early childhood education strategy : Full-day universal pre-K for four-year-olds ; Targeted educare/abecedarian for all disadvantaged children ; Nurse family partnership for all disadvantaged first-time mothers ; Costs ; Aggregate benefits ; Accountability and quality improvement ; What level of government should be responsible for early childhood education? ; Concluding comments -- 8. Why early childhood education makes sense now: ECE's place in the ongoing struggle for broader economic opportunities : Labor supply and labor demand ; History matters ; The continuing argument over expanding educational access ; But why early childhood education? And why now? ; Doing the good we know how to do.
Description based on print version record.
Keywords: Education, Preschool -- Economic aspects; Education, Preschool; Early childhood education -- Economic aspects; Early childhood education; EDUCATION -- Preschool & Kindergarten; Education, Preschool -- United States; Early childhood education -- United States; Education, Preschool -- Economic aspects -- United States; Early childhood education -- Economic aspects -- United States; United States; Electronic books